Transformation of Fulvia fulva, a fungal pathogen of tomato to Hygromycin B resistance - Oliver, Richard; Roberts, I.; Harling, R.; Kenyon, L.; Punt, P.; Dingemanse, M.; Van Den Hondel, C. (1987)
A transformation system for the tomato pathogen Fulvia fulva has been developed. Hygromycin B resistant colonies were obtained after treatment of protoplasts with a plasmid containing an E. coli hygromycin B phosphotransferase gene fused to an Aspergillus nidulans promoter. The DNA was stably integrated into the genome. The number and sites of integrations varied among transformants. The demonstration of transformation opens the way for the molecular genetic analysis of the interaction of Fulvia with tomato.